ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Khairunisa Umairah (2021)
The purpose of this research is to determine the effect of Profitability proxied by Return on Equity, Capital Structure proxied by Debt to Equity Ratio, and Firm Size proxied by the logarithm natural of total assets on Firm Value proxied by Price to Book Value. The population of this research is consumer goods companies that generate profit and listed on the Indonesia Stock Exchange for the 2018-2020 period. The sample technique used is a saturated sample, so that 32 consumer goods companies are obtained for the 2018-2020 period with a total of 96 sample data. This research is quantitative which is tested through E-Views 11 using Panel Data Regression Analysis Method with a significance level of 5%. The results of this study are (1) there is positive effect between Profitability and Firm Value, (2) there is positive effect between Capital Structure and Firm Value, (3) there is a negative effect between Firm Size and Firm Value.